KEEPING A JOURNAL " THE USE OF A DIARY IN TEACHING RECOUNT TEXTS TO IMPROVE STUDENTS' WRITING ABILITY" : A QUASI-EXPERIMENTAL STUDY OF EIGHTH GRADE STUDENTS AT SMPN 1 LEMBANG - Chitra Setia Prantama, - (2010)
This study attempts to examine the effectiveness of writing a diary in teaching recount texts to improve students' writing ability among the second graders of SMPN 1 Lembang. A quasi-experimental design with a pretest and a posttest was used in conducting the research. The two classes were selected to be the samples of this research: experimental group and control group.The treatments were given in six sessions and writing recount text was used as research instrument in the pretest and the posttest. Then, the scores of both groups were analyzed by using an independent t-test. The result scores of independent t-test showed that the experimental group students had higher writing scores (M =76.67, SE = 0. 568) than the control group students (M = 74.63, SE = 0.663). The students' writing ability in both groups was significantly different as indicated by t (58) = 2.328 and sig. = .000, p < .05 with a large effect size (r = 0. 945). In addition, the students' responses from the interview also showed that writing a diary improve students' writing ability in term of enriching vocabulary, building self-confidence, and motivating them to learn English. In other words, the research findings confirmed that writing a diary was effective in improving students' writing ability.